Kazalci urbanega razvoja po načelu trajnosti - Šašek-Divjak, Mojca (Urbani izziv, 1998)
Development in space reflects the consequences of development decisions in all areas of life and work. For this purpose all questions with regard to spatial planning should be solved comprehensively, in connection with economic and social development, while taking into consideration natural potentials and limitations and observing the principles for sustainable balanced development. To measure the sustainability of a place a series of indicators have to be devised. An example of the use of these indicators is presented.
Keywords: mesta; razvojna strategija; sustainable development; trajnostni razvoj; urbana naselja